ANALISIS KONSENTRASI PENGANGGURAN PROVINSI DAN FAKTOR YANG MEMPENGARUHINYA DI INDONESIA TAHUN 2007-2011 - Sri Rahayu Budi Hastuti; Wahyu Dwi Artaningtyas (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: This study aims to analyze the province unemployment concentration and to analyze the influence of economic growth, investment growth, population growth and wage growth to the province unemployment concentration in Indonesia. The data used are secondary data taken from the provinces in Indonesia at 2007-2011. To analyze the province unemployment concentration used value of concentration index and to analyze the influence of economic growth, investment growth, population growth and wage growth to province unemployment concentration used multiple regression with panel data. Results of the research from the average value of concentration index shows that 12 provinces from the 33 provinces in Indonesia are the unemployment basis (NAD, North Sumatra, West Sumatra, Riau, Riau Islands, DKI Jakarta, West Java, Banten, East Kalimantan, North Sulawesi, South Sulawesi and Maluku). Results of the panel data regression of 4 factors included in the model only economic growth influence to province unemployment concentration in Indonesian. Keywords: Unemployment Concentration, Concentration Index, Economic Growth, Investment Growth, Population Growth, Wage Growth.